EFFECT OF ENVIRONMENTAL STRESS ON HUMAN HEALTH - Godha, Sonal (International Journal of Research -GRANTHAALAYAH, 2015)
Over the past three or four decades, there have been important advances in the understanding of the actions, exposure-response characteristics, and mechanisms of action of many common air pollutants. Environmental physiology is the study of the physiological mechanisms that allow animals to cope with and adapt to changes in temperature, humidity, atmospheric pressure, and other natural factors of their physical environment these ideal test conditions are clearly not representative of the fluctuations in the natural environment encountered by humans and other animals on a day-to-day basis. How variations in the natural environment will alter physiological responses to toxicants. Temperature and exercise are the two well-studied parameters in the fields of environmental physiology and toxicology. In general, high temperatures exacerbate the toxic effects of many environmental toxicants. Quantitative and qualitative understanding of the effects of a small group of air pollutants/ toxicants has advanced considerably, but the understanding is by no means complete, and the breadth of effects of all air pollutants is only partially understood. The prospect of global warming also warrants a better assessment of how higher environmental temperatures may impact on the response of humans and other species to toxic chemicals. Hence, this paper focuses on the salient aspects of the interaction between environmental stress and physiological response to toxic agents with particular emphasis on temperature.